2007
DOI: 10.1590/s0034-89102007000600005
|View full text |Cite
|
Sign up to set email alerts
|

Infestação de área urbana por Aedes aegypti e relação com níveis socioeconômicos

Abstract: OBJECTIVE:To assess the association between Aedes aegypti larvae infestation rates and socioeconomic factors. METHODS:Infestation rates in the urban area of the city of São José do Rio Preto, Southeastern Brazil, were calculated in January of 2005 and subsequently geocoded by address. The urban census tracts were grouped by means of main component analysis, thus producing four socioeconomic clusters (1-4, in a decreasing order of socioeconomic level) and a fi fth cluster (5) with a level below the others and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 12 publications
2
24
0
6
Order By: Relevance
“…aegypti larvae was observed by Ferreira and Chiaravalotti Neto [28] at the county of São José do Rio Preto, São Paulo State, Brazil.…”
Section: Discussionmentioning
confidence: 93%
“…aegypti larvae was observed by Ferreira and Chiaravalotti Neto [28] at the county of São José do Rio Preto, São Paulo State, Brazil.…”
Section: Discussionmentioning
confidence: 93%
“…Alguns autores abordam a relação entre variáveis relacionadas às condições de vida da população e a ocorrência da dengue; entretanto os resultados encontrados são divergentes 13,14,15,16,17 . A maioria destes estudos utilizou metodologia em que as variáveis relativas às condições de vida foram abordadas num mesmo nível, não contemplando o contexto social enquanto unidade complexa, no qual fatores sócio-culturais e estruturais urbanos geram uma realidade única em cada local, favorecendo ou não a disseminação da dengue.…”
Section: Introductionunclassified
“…Studies in the city of São José do Rio Preto, in São Paulo, showed total independence between infestation assessed through the Bretau index, building index and container index, and socio-economic conditions in the four city districts 17 . However, the levels of infestation in the city were higher in areas with a lower socio-economic level and deficient sanitary infra-structure.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, given that vector control depends essentially on the level of involvement of the population in daily actions to eliminate breeding pools, populations with a better level of schooling and income would be expected to live in neighborhoods with lower or null building infestation rates. However, other factors may change this expectation, as, for example, a higher number of containers with breeding potential, such as not regularly treated swimming pools, large badly sealed water reservoirs, vases, types of plants used in gardening and ornaments, fountains, and others [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%